Answer:
Step-by-step explanation:
The max value that this function reaches is 6, and the function reaches this value repeatedly, beginning at x = 0 and then at x = 6, 12, 15, etc. This tells us that the period of the function is 6.
The function is increasing on (3, 6), (9, 12), and so on
The function is even because the graph is symmetrical about the y-axis.
Answer:
3(3x+1) (2x-1)
Step-by-step explanation:
18x^2 -3x-3
Factor out a 3
3(6x^2 -x-1)
3(3x+1) (2x-1)
Answer:
(3x - 1)(4x - 3)
Step-by-step explanation:
separating terms it will look like this
(3x - 1)(4x - 3)
when multiple each numbers you will see it will form up as 12x^2 -13x + 3
Answer:
It should be 147
Step-by-step explanation:
Option A
The solution is ![(0, \frac{-1}{4})](https://tex.z-dn.net/?f=%280%2C%20%5Cfrac%7B-1%7D%7B4%7D%29)
<em><u>Solution:</u></em>
<em><u>Given system of equations are:</u></em>
3x + 6y = 1 ------ eqn 1
x - 4y = 1 ------ eqn 2
We have to find solution to system of equations
We can use substitution method
From eqn 2,
x = 1 + 4y -------- eqn 3
Substitute eqn 3 in eqn 1
3(1 + 4y) + 6y = 1
3 + 12y + 6y = 1
18y = 1 - 3
18y = -2
Divide both sides by 18
![y = \frac{-2}{18}\\\\y = \frac{-1}{4}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B-2%7D%7B18%7D%5C%5C%5C%5Cy%20%3D%20%5Cfrac%7B-1%7D%7B4%7D)
Substitute the above value of y in eqn 3
![x = 1 + 4 \times \frac{-1}{4}\\\\x = 1-1\\\\x = 0](https://tex.z-dn.net/?f=x%20%3D%201%20%2B%204%20%5Ctimes%20%5Cfrac%7B-1%7D%7B4%7D%5C%5C%5C%5Cx%20%3D%201-1%5C%5C%5C%5Cx%20%3D%200)
Thus solution is ![(0, \frac{-1}{4})](https://tex.z-dn.net/?f=%280%2C%20%5Cfrac%7B-1%7D%7B4%7D%29)